Toxicological chemistry and biochemistry - Manahan, Stanley E. (Lewis Publishers, 2003)
Chemistry and organic chemistry.--Environmental chemistry.--Biochemistry.--Metabolic process.--Environmental biological processes and ecotoxicology.--Toxicology.--Toxicological chemistry.--Genetic aspects of toxicology.--Toxic responses.--Toxic elements.--Toxic inorganic compounds.--Organometallics and organometalloids.--Toxic organic compounds and hydrocarbons.--Organooxygen compunds.--Organonitrogen compounds.--Organohalide compounds.--Organosulfur compounds.--Organophosphorus.--Toxic natural products.--Analysis of xenobiotics.--